(untitled) (Al Basirah, 2020)
The personality of the messenger, before and after prophethood was admired by both; friends and foes. whoever learned or read about him without prejudice is bound to lose skepticisim, and not hesitate to appreciate his greatness, acknowledge his favours, and follow his path, for the bright lights of his persona(s.a.w) dissipates the darkness of shirk and Ignorance,softens the stiffness of hearts, makes orphans forget the bitterness of their plight, the bereavedـــ the pain of bereavement,the needyـــ the stings of want, and the weak ـــthe weight of indignity. Despite being met with great harm from those closest to himself; his relatives, he chose patience and kindness. He knew no injustice nor cajolery. He was kind and courteous to his neighbors, a step shy of bequeathing them. He commanded children be kind to their parents even if they were Mushrik. He emphasized on mothers, for they are delicate, and more deserving of care and kindness. Women were honored and enjoyed a distinguished place, as the Prophet had returned to them their forsaken humanity during the preceeding dark era in which they held no significance. His favors weren’t exclusive to his wives but extended to include all women, Muslim or otherwise, he treated them with kindness and called them“AlQawareer”(Glass flasks) for they are pure and delicacte. He corrected them when they erred, and equated men who toil to meet their needs with those who fend off enemies on fronts. He commanded in his last moments that women be treated righteously. The French orientalist, Lewis Seidio, was impressed by the personality of the prophet(s.a.w)and the manner in which he conducted himself and treated other people, which induced them to call him “the truthful, the honest”, until he was entrusted with the message and began calling his people to the one true god, to which they opposed him viciously, but heeded his call eventually. He was kind to the elderly,tender to the young, a teacher and a wise man in service of his society, a stream of knowledge and manners to the whole world. this paper discuses in detail those traits.